2009
DOI: 10.1111/j.1462-2920.2008.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel sulfur‐oxidizing streamers thriving in perennial cold saline springs of the Canadian high Arctic

Abstract: SummaryThe perennial springs at Gypsum Hill (GH) and Colour Peak (CP), situated at nearly 80°N on Axel Heiberg Island in the Canadian high Arctic, are one of the few known examples of cold springs in thick permafrost on Earth. The springs emanate from deep saline aquifers and discharge cold anoxic brines rich in both sulfide and sulfate. Grey-coloured microbial streamers form during the winter months in snow-covered regions of the GH spring run-off channels (-1.3°C to 6.9°C,~7.5% NaCl, 0-20 p.p.m. dissolved su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 76 publications
4
48
0
4
Order By: Relevance
“…Further work identified culturable microbes from the spring sediments with autotrophic and sulfur-oxidation activities (Perreault et al, 2008), and the small amounts of hydrocarbons in gases exsolving from these springs were compositionally and isotopically consistent with microbial methanogenesis and possible methanotrophy (Perreault et al, 2007). Niederberger et al (2009) characterized gray-colored microbial streamers that form during the winter months in the snow-covered regions of the GH spring runoff channels. Culture, molecular and microscopicbased analysis of the 16S rRNA gene indicated that the streamers were dominated by chemolithoautotrophic sulfur-oxidizing Thiomicrospira species that oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions (Niederberger et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Further work identified culturable microbes from the spring sediments with autotrophic and sulfur-oxidation activities (Perreault et al, 2008), and the small amounts of hydrocarbons in gases exsolving from these springs were compositionally and isotopically consistent with microbial methanogenesis and possible methanotrophy (Perreault et al, 2007). Niederberger et al (2009) characterized gray-colored microbial streamers that form during the winter months in the snow-covered regions of the GH spring runoff channels. Culture, molecular and microscopicbased analysis of the 16S rRNA gene indicated that the streamers were dominated by chemolithoautotrophic sulfur-oxidizing Thiomicrospira species that oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions (Niederberger et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…These springs are among the only known cold springs in thick permafrost on Earth (Andersen et al, 2002) and the geomorphology, chemistry, thermal environment and microbiology of two sets of moderately cold, saline springs (Gypsum Hill (GH), Colour Peak (CP)) located at Expedition Fiord on AHI have been extensively studied (Pollard et al, 1999;Andersen et al, 2002;Perreault et al, 2007Perreault et al, , 2008Niederberger et al, 2009). These springs flow throughout the entire year with constant discharge temperatures ranging from À0.5 to 6.9 1C, and discharge waters that are moderately saline (7.5-15.8% salts), anoxic (mean oxido-reduction potential (ORP) of À325 mV), near-neutral (pH 6.9-7.5), rich in both sulfate (2300-3724 mg l À1 ) and sulfide (25-100 p.p.m.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lay et al (2012) also reported phylotypes related to methanogenesis, methanotrophy, sulfur reduction and oxidation Average perennial water temperature at outlets À5.9 to À4.7°C (Lay et al, 2012) 3.6°C (Pollard et al, 1999) 3.9°C (Pollard et al, 1999) Salinity 22-26% (Lay et al, 2012), 22.4% (this study) 16-17% (Pollard et al, 1999), 16.6% (this study) 8-9% (Pollard et al, 1999) (Perreault et al, 2007;Omelon et al, 2006) 27.92 g/L Na, 2.11 g/L Ca, 44.21 g/L Cl (Perreault et al, 2007;Omelon et al, 2006) Discharging gases (bubbles) 50% thermogenic CH 4 , 35% N 2 , 10% CO 2 , <5% He, H 2 , other hydrocarbons (Niederberger et al, 2010) >98% N 2 , <1% CH 4 , <1% CO 2 , minor O 2 (Pollard et al, 1999) >98% N 2 , <1% CH 4 , <1% CO 2 , minor O 2 (Pollard et al, 1999) Microbiology Low microbial diversity compared to similar cryo-environments Psychrophilic obligately chemolithoautotrophic S oxidizing bacteria; anaerobic S and SO 4 reducing bacteria (Perreault et al, 2007) Anaerobic heterotrophic, and aerobic autotrophic S oxidizing bacteria; anaerobic S and SO 4 reducing bacteria; methanogens; possible methanotrophs. Streamers: S-oxidizing bacteria (Perreault et al, 2007(Perreault et al, , 2008Niederberger et al, 2009) Anaerobic methanotrophs; methanogens; S oxidizing bacteria; ammonia-oxidizers; possible SO 4 reducing archaea (Niederberger et al, 2010;Lay et al, 2012) and an archaeal community dominated by phylotypes most closely related to ammonia-oxidation. Although some authors have referred to this site as the ''Lost Hammer spring'', it was mapped by Harrison and Jackson (2008) as ''Wolf spring''.…”
Section: The Wolf Spring Sitementioning
confidence: 99%